Dietary urbanization destabilizes host-gut microbiome homeostasis and informs precision nutrition for human health - Zhang, Fen; Zhou, Guicheng; Schewe, Matthias; Kulling, Sabine E.; Ding, Yu; Mozaffarian, Dariush; Zuo, Tao (Cell metabolism, 2025)
Since the industrial revolution, human dietary habits have invariably trended toward dietary urbanization, during which the human gut microbiota has rapidly changed. However, the human genome cannot change substantially over one generation, leaving it potentially ill-equipped to adapt to evolving microbial functions associated with rising non-communicable diseases (NCDs). In this review, we map the chronological alterations in dietary patterns and incidences of NCDs during global urbanization while emphasizing the gut microbiome as the centerpiece. We then illustrate losses and acquisitions of gut microbes during worldwide urbanization and delineate the mechanisms by which urbanized diets may disrupt host-microbiome interactions, linking to the onset of NCDs. Building on this, we further propose a microbiome-directed precision-nutrition framework that integrates both inter-population and intra-population variations to promote diet-fueled host-microbiome synergism and hence to counteract urbanization-associated diseases. These insights will instruct future microbiome-targeted diets to thwart NCDs.